Genetic barcoding resolves the historically known red alga Champia parvula from southern New England, USA, as C. farlowii sp. nov. (Champiaceae, Rhodymeniales) - Griffith, Maura K.; Schneider, Craig W.; Wolf, Daniel I.; Saunders, Gary W.; Lane, Christopher E. (Phytotaxa, 2017)
Using mitochondrial COI-5P and plastid rbcL genetic markers, the red algal species historically known in southern New England, USA, as Champia parvula is found to be genetically distinct from the species to which it has historically been aligned. This necessitates the description of a new species, C. farlowii, for plants from Rhode Island, Massachusetts, Connecticut and New York, USA. The new species is morphologically compared with true European C. parvula and congeners, especially those with similar features previously aligned under the same species name. Champia farlowii is a morphologically cryptic species, the sixth in the expanding C. parvula complex, with overlapping characteristic measurements despite differences at the range extremes, when compared to C. parvula.